Determination of the rheological properties of drilling fluids from rotational viscometry data - Myslyuk, M. A. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2020)
The method of rotational viscometry data processing, which is based on the maximum likelihood function principle is considered. The method takes into account the informative content of experiments and is built on the strict solution of the Couette flow equation in a viscosimeter gap. The class of models is formed from rheologically stationary (including viscosity) models. A generalization of the model for processing the experimental plan data with the aim of building equations of the state of the rheological properties of variable factors is considered. A multicriterial interpretation of estimates of the rheological model and properties of liquids has been proposed. Illustrative examples of estimating rheological properties building of drilling fluids and their equations of state are given.